Efektivitas Komunikasi Interpersonal antara Guru dengan Anak Autis di Biro Psikologi Psikodinamika Banda Aceh - Wahyuni Wahyuni (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2017)
This study entitled Interpersonal Communication Effectiveness between Master and Autistic Children in Psychology Bureau Psychodinamika Banda Aceh. This study aims to describe and discuss how the effectiveness of interpersonal communication in the learning process between teachers with children Autism in Psychological Bureau of Psychodynamics. In this study the researcher uses Symbolic Interaction Theory. Researchers use descriptive qualitative research methods. Data collection techniques through the process of direct observation at the place of research, and by conducting interviews with teachers and dang autistic children. Data analysis is done qualitatively by connecting interpersonal communication of teacher with behavior of child of Autis. The results show that the effectiveness of Interpersonal communication between Master and Autistic Children in the learning process is effective when teachers communicate using media aids such as puzzle cards, toy cards and toys. It is seen based on indicator of effectiveness of interpersonal communication that is, empathy, supportive attitude, positive attitude, openness and equality.